Ilmu Balaghah Sebagai Embrio dalam Dunia Dakwah - A. Fajar Awaluddin (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2019)
Abstract             Da'wah is a form of religious communication whose main purpose is amar ma'ruf and nahi munkar with object of da'wah, mad'u, either in the form of individual or group. Da'i as da'wah perpetrators are required to master the da'wah material to be submitted to mad'unya, which includes the problem of aqidah, shariah, muamalah, and morality. As for the source of da'wah material that is the Qur'an and hadith which is the source of the highest teachings and sources of Islamic law. The existence of Arabic in da'wah becomes so important because the two material sources of the da'wah use Arabic, so Arabic is the key to the opening of Islamic knowledge. To examine and depth it also requires mastery of various branches of science such as Science Tafsir, Nahwu Science, Bayan Science, Ushul Fiqih, etc., which is not far from Arabic. In addition, the original literary books which are the product of thought, interpretation, syarahan of the Qur'an and hadith by the scholars of the past written in Arabic, all of which are part of the source of da'wah material that should be known by the da "i . All that aims for the delivery of da'wah material sourced from the Qur'an and hadith in accordance with Islamic Shari'a and distanced from misunderstanding of understanding received by the mad'u in receiving messages conveyed by a da'i. Kata Kunci: Islam, Qur'an, Balghah and Da'wah